IMPLEMENTASI PROGRAM PEMBERDAYAAN PEREMPUAN MELALUI SEKOLAH PEREMPUAN (SEKOPER) DI DESA KRAMATINGGIL KABUPATEN GRESIK - Mutiara Shofiyyahtusya'diah; Tjitjik Rahaju (Universitas Negeri Surabaya, 2022)
Transformation through women's empowerment involved all components of society so women will become more empowered. Gresik is one of the regional governments that cares about women's empowerment issues. This is realized by the issuance of Regional Regulation of Gresik District No. 4 of 2012 into the Sekoper program, one of which is located in Kramatinggil Village. Unfortunately, some individuals in the targetted group are still unaware of this program. The goal of this research aims to determine how the Sekoper was implemented in Kramatinggil Village. This is a descriptive qualitative study. The focus of this research is analyzing content of policy and context of implementation by Grindle. Data were collected through observation, documentation, interviews, and literature studies. The data analyzed by collecting, reducting, presentation, and concludes. The actors in this program are KPS2K and KBP3A. According to this research findings, the policy is being implemented through a variety of programs tailored to environmental conditions in Kramatinggil Village. The implementation of Sekoper is not running optimally because several lack of human resources, finance, and lack of program socialization. Researchers recommend that implementers should focused in best practice programs, monitored the program trough supervisor, increase APBD fund allocation, and implement a merit system. Keywords: Women's Empowerment, Participation, Public Policy.